Fix Desalination System Technology as Development of Creative and Innovative Capabilities of Youth Community - Eko Prayetno; Risandi Dwirama Putra; Dedy Kurniawan; Edwin Ghutowo; Soedrajad Haryo Adji; Ricky Try Noer Hidayah; Adih Adih (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2019)
Community service activity is conducted in the region of KKN-PPM Universitas Maritim Raja Ali Haji (UMRAH) in the Malang Rapat Village, Bintan Regency.  Malang Rapat Village was chosen because of the location on the coastal area and have a concern about the management of hydrology, clean water resources and the management of limited water resources.  The lack of information and transfer of knowledge to the community in the coastal areas will produce some difficulties to solve the problems, especially in solving the problems regarding the adequacy and need for clean water. Then the general condition of the youth village in the coastal areas is not goal oriented. Based on those exercising their Community Services activities are carried out using the learning development by including the principle of 4C (Creative, Collaborative, Communicative and Competitive). It is expected that with the development of scientific principles that incorporate the principle of the transfer of the value of creativity, collaborative, communicative and competitive will give a very good impact to the target object for the long term. In this case, appropriate technology was designed for a public event in the Region KKN-PPM Malang Rapat Village in helping to resolve the problem of clean water needs for consumption is making Fix Desalination System. Fix Desalination System designed structure mica glass/acrylic which has a volume of 1 m3 to produce 15.95 ml distilled fresh water in the tank within 6 hours.